2019
DOI: 10.23736/s0025-7826.18.03294-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time-of-day strength training on plasma testosterone and cortisol concentrations in male amateur athletes

Abstract: BACKGROUND:The purpose of the present study was to examine the effects of time-ofday-strength training on plasma testosterone (T) and cortisol (C) concentrations in male amateur athletes. METHODS: Forty five male athletes (age, 21.2±0.3 years; height, 1.75±0.14 m; weight, 72±1.52 kg) participated in the present study. They were subjected to strength training of the knee extensor and flexor muscles. Following this, they were randomly assigned into three groups: morning strength training group (MSTG, 07:00-08:00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The differences in T production between men and women might explain the higher prevalence of the disease in women (Picanco et al, 2018). T is a steroid hormone secreted by the Leydig cells of the testes under hypothalamic and pituitary control defining the hypothalamo-pituitary-testicular (HPT) axis and in small amounts from the adrenal cortex (Bouazizi et al, 2019). In both sexes, T follows a diurnal rhythm with peak concentrations occurring in the morning followed by a progressive decline over the course of the day, rising again at night during sleep (Bouazizi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in T production between men and women might explain the higher prevalence of the disease in women (Picanco et al, 2018). T is a steroid hormone secreted by the Leydig cells of the testes under hypothalamic and pituitary control defining the hypothalamo-pituitary-testicular (HPT) axis and in small amounts from the adrenal cortex (Bouazizi et al, 2019). In both sexes, T follows a diurnal rhythm with peak concentrations occurring in the morning followed by a progressive decline over the course of the day, rising again at night during sleep (Bouazizi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…T is a steroid hormone secreted by the Leydig cells of the testes under hypothalamic and pituitary control defining the hypothalamo-pituitary-testicular (HPT) axis and in small amounts from the adrenal cortex (Bouazizi et al, 2019). In both sexes, T follows a diurnal rhythm with peak concentrations occurring in the morning followed by a progressive decline over the course of the day, rising again at night during sleep (Bouazizi et al, 2019). Many studies have also reported a link between low T levels and the risk of developing AD which is the leading cause of dementia (Lei and Renyuan, 2018).…”
Section: Introductionmentioning
confidence: 99%